1995
DOI: 10.1210/jcem.80.1.7829637
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 gene polymorphism associated with Graves' disease in a Caucasian population.

Abstract: Graves' disease (GD) is an autoimmune thyroid disease. Multiple genetic factors are believed to be involved in its pathogenesis, but the factors are largely unknown, except for sex (female disease preponderance) and the role of human leukocyte antigen (HLA) genes on chromosome 6. To understand the mechanisms underlying the development of GD, a search for non-HLA-linked genes is crucial, and we tested several candidate genes, including the CTLA-4 gene on chromosome 2q33. CTLA-4 molecules may either facilitate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
194
2
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(209 citation statements)
references
References 0 publications
7
194
2
6
Order By: Relevance
“…A distribution analysis of the soluble and full-length CTLA-4 transcripts among the CD4 and CD8 subsets of T cells has demonstrated that CD4 cells express both transcripts at the same level, whereas CD8 cells appear to express nearly 2.5-fold more full-length product with respect to sCTLA-4 [10,20,53]. An analysis of the association between the sCTLA-4 mRNA level and exon 1 +49A/G and CT60A/G CTLA-4 gene polymorphisms in healthy subjects also showed that the sCTLA-4 mRNA level in unstimulated CD4 T cells is higher for allele A at position +49 and the CT60 A variant [29].…”
Section: Soluble Form Of Ctla-4mentioning
confidence: 94%
See 1 more Smart Citation
“…A distribution analysis of the soluble and full-length CTLA-4 transcripts among the CD4 and CD8 subsets of T cells has demonstrated that CD4 cells express both transcripts at the same level, whereas CD8 cells appear to express nearly 2.5-fold more full-length product with respect to sCTLA-4 [10,20,53]. An analysis of the association between the sCTLA-4 mRNA level and exon 1 +49A/G and CT60A/G CTLA-4 gene polymorphisms in healthy subjects also showed that the sCTLA-4 mRNA level in unstimulated CD4 T cells is higher for allele A at position +49 and the CT60 A variant [29].…”
Section: Soluble Form Of Ctla-4mentioning
confidence: 94%
“…The CTLA4 locus is the only non-HLA locus for which the association with GD has been repeatedly demonstrated since 1995, when the first evidence for an association with the CTLA-4 3′-UTR-microsatellite in a Caucasian population was reported [29]. Linkage and association of the CTLA-4 exon 1 polymorphism with GD, and to lesser extent with HT, has been found in several populations, although there seems to be some inconsistency, probably due to population heterogeneity [11,17,27,[30][31][32][33] (Table 1).…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…8 There have been several reports demonstrating an association between the cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) gene and the AITDs 6,9-25 ( Table 1). The association between GD and a CTLA-4 3 0 untranslated region (3 0 UTR) microsatellite (AT repeat) and an A/G single-nucleotide polymorphism (SNP) at position 49 in the CTLA-4 leader peptide (A/G 49 ) has been consistent across populations of different ethnic backgrounds, such as Caucasians, 6,9,10,[14][15][16][17] Chinese, 11 Japanese, 13,22 and Koreans. 23 The association of CTLA-4 and GD has also been confirmed in a family-based study using transmission disequilibrium test (TDT) analysis.…”
Section: Introductionmentioning
confidence: 97%
“…9 Furthermore, B7 blockage using anti-B7 antibodies or CTLA-4Ig can prevent the development of murine experimental autoimmune encephalomyelitis (EAE), a T cellmediated autoimmune disease that shares many clinical and histological features with human MS. [10][11][12][13] It was considered possible that structural variations as well as the dysregulation in the expression of the costimulatory molecules may be associated with susceptibility to autoimmune or chronic inflammatory diseases. It was reported that polymorphism within CTLA-4 exon 1 (49A/G) and that of the dinucleotide repeats within 3′-untranslated region (3′-UTR) seemed to be significantly associated with insulin-dependent diabetes mellitus (IDDM), 14,15 Graves' disease 16,17 or Hashimoto's thyroiditis. 18 Moreover, a genome-wide linkage study reported 2q33 and 3q13 as candidate chromosomal regions for rheumatoid arthritis (RA), which are adjacent to the loci where CD28 and CTLA-4, CD80 and CD86 are localized, respectively.…”
Section: Introductionmentioning
confidence: 99%